EFEKTIVITAS PELAYANAN BANDAR UDARA SILAMPARI KOTA LUBUKLINGGAU SUMATERA SELATAN - Fisip PAsira; Eddy Norman Setiawan (Jurnal PAsira, 2020)
ABSTRACT This study aims to determine in depth about the effectiveness of services at Silampari Lubuklinggau Airport. This study uses a qualitative descriptive method with data collection techniques, observation, interviews, documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing / verification. The results of this study indicate that the service effectiveness of Silampari Lubuklinggau Airport is quite effective because it has recapitulated and evaluated flight schedules between the permitted schedules and the implementation schedule, completing airport facilities and infrastructure and paying attention to its workers. As well as employees have worked according to their respective main functions such as the Avsec unit taking care of security issues, while safety is also taken care of by the PKP-PK, and for the terminal is also taken care of by the terminal, this is that every employee at Silampari Lubuklinggau Airport has worked according to his position . Providing excellent service in accordance with the main tasks and functions by preparing operational materials and services for passenger terminal facilities, cargo and support, and carrying out supervision and control of airport minimum services, as well as flight information. Keywords: Effective; Security Service ABSTRAK Penelitian ini bertujuan untuk mengetahui secara mendalam tentang Efektivitas Pelayanan Di Bandar Udara Silampari Lubuklinggau. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data observasi, wawancara, dokumentasi. Teknik analisa data yang digunakan reduksi data, penyajian data dan Penarikan Kesimpulan/Verifikasi. Hasil penelitian ini menunjukkan bahwa Efektivitas pelayanan Bandara Silampari Lubuklinggau cukup efektif karena sudah melakukan rekapitulasi dan evaluasi jadwal penerbangan antara jadwal yang diijinkan dengan jadwal pelaksanaan, melengkapi sarana dan prasarana bandara serta memperhatikan pekerjanya. Serta pegawai sudah berkerja sesuai tugas pokok fungsinya masing-masing seperti unit Avsec mengurusi permasalahan keamanan, sedangkan keselamatan juga diurusi oleh pihak PKP-PK, serta untuk diterminal juga diurusi oleh pihak terminal hal ini setiap pegawai yang ada di Bandara Silampari Lubuklinggau sudah berkerja sesuai jabatanya. Memberikan pelayanan prima sesuai Tupoksi dengan menyiapkan bahan pelaksanaan pengoperasian dan pelayanan fasilitas terminal penumpang, kargo dan penunjang, dan melaksanakan pengawasan dan pengendalian pelayanan minimal Bandar Udara, serta informasi penerbangan. Kata Kunci: Efektifitas; Pelayanan Keselamatan